RAGE is a potential biomarker implicated in immune infiltrates and cellular senescence in lung adenocarcinoma. Issue 5 (31st March 2022) - Lin, Zhihui; Yu, Biyun; Yuan, Li; Tu, Jinjing; Shao, Chuan; Tang, Yaodong
Abstract: Background: Receptor for Advanced Glycation End‐products (RAGE) is an oncogene abnormally expressed in various cancers. However, the clinical value of RAGE and the biological role of RAGE in lung cancer have not been fully investigated. Methods: We compared the RAGE expression using several public databases. The relationship between RAGE expression and clinicopathological variables was assessed. The R software package was used to carry out enrichment analyses of RAGE co‐expression and gene set enrichment analysis (GSEA). Additionally, we used the TIMER database to assess the association between immune infiltration and RAGE expression. The correlation between RAGE expression and senescence biomarkers in lung adenocarcinoma was analyzed using the TCGA database. Results: Our findings indicated that the expression of RAGE was downregulated in lung adenocarcinoma, and down‐regulation of RAGE was related to poor overall survival and disease‐free survival. Functional enrichment analysis indicated that RAGE co‐expression genes were mainly associated with neutrophil activation involved in immune response, neutrophil degranulation, and regulation of leukocyte‐mediated immunity. Correlation analysis revealed that RAGE expression was closely related to the purity of the tumor and immune infiltration. GSEA indicated that the RAGE‐related differential genes were mainly enriched in senescence‐related pathways. Besides, the RAGE expression was significantly associated with senescence‐related genes. Conclusion: Down‐regulation of RAGE expression was associated with poor prognosis, as well as defective immune infiltration and cellular senescence in lung adenocarcinoma. Abstract : We compared the AGER expression using several public databases. The relationship between AGER expression and clinicopathological variables was assessed. R software package was used to carry out enrichment analyses of AGER co‐expression and gene set enrichment analysis (GSEA). Additionally, we used TIMER database to assess the association between immune infiltration and AGER expression. The correlation between AGER expression and senescence biomarkers in lung adenocarcinoma was analyzed using TCGA database.